The Implementation of Pancasila Values in Cyberbullying Cases Among Students - Situmeang, Marisa; Syakirina, Azza; Sidabutar, Putri; Gultom, Theresia; Pulungan, Khoirul (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2025)
The development of science and technology (science and technology) in the digital era has brought fundamental changes in the way people interact and communicate. However, behind the convenience and benefits offered, the phenomenon of cyberbullying has emerged that is increasingly rapid, showing that there is a gap between technological advances and the application of Pancasila values in digital life. Pancasila as the basis of the state has values that can be a solution in suppressing cyberbullying, especially in building a more ethical and responsible digital culture. The goal is to analyze the extent to which Pancasila values can be applied in suppressing cyberbullying cases in Indonesia as well as strategies that can be used to increase public awareness of the importance of ethics in social media. This study uses aliterature study method with the type of research used is descriptive qualitative research. The data used in this study issecondary data obtained from various reference sources such as books, journals, articles and other scientific works that canbe accounted for. The results of the study show that cyberbullying in schools occurs in various forms, such as physical insults through messages or uploads on social media. The students are aware of the negative impact of cyberbullying, such as psychological distress and low self-confidence, so some of them choose to report the case to the school or give a direct reprimand to the perpetrator